PROBLEMS OF TRANSLATING POETRY - Gafurova Nozimaxon Ikramovna (Лучшие интеллектуальные исследования, 2024)
Translation is a form of literary creation that involves the reproduction of a text in one language into another, and translation is the most important form of interethnic communication. Among translation issues, poetry translation is the most problematic area challenging both translators and authorities in the field of translation studies. Translation of poetry as a yet unanalyzed 'black. box (Francis 2006) has been a much debated issue since olden times, with many pros and cons and dichotomist reasoning as to its possibility or impossibility.This article describes about translation of poetry and and analyzes problems of poetic translation.